2015
DOI: 10.1182/blood-2015-01-624239
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the case for genetically engineered mouse models in human myelodysplastic syndrome research

Abstract: Key Points• With a few exceptions, the histologic and cytologic characteristics of myelodysplasia are similar in humans and mice.• As in humans, MDS and MDS/MPN are distinct diseases in mice; mouse models of these diseases can serve as useful research tools.Much-needed attention has been given of late to diseases specifically associated with an expanding elderly population. Myelodysplastic syndrome (MDS), a hematopoietic stem cell-based blood disease, is one of these. The lack of clear understanding of the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 95 publications
4
38
0
Order By: Relevance
“…Primary human MDS cells grow poorly in most mouse models and highly specific and genetically engineered mouse models are required to study human MDS in the xenograft setting (Zhou et al , 2015). Consequently, to functionally assess the self‐renewal potential of both the CLEC12A positive CD34 + CD38 − cells and the CD34 + CD38 − cells lacking CLEC12A expression, four MDS patients with known clonal cytogenetic abnormalities were selected for studies in the LTC‐IC assay.…”
Section: Resultsmentioning
confidence: 99%
“…Primary human MDS cells grow poorly in most mouse models and highly specific and genetically engineered mouse models are required to study human MDS in the xenograft setting (Zhou et al , 2015). Consequently, to functionally assess the self‐renewal potential of both the CLEC12A positive CD34 + CD38 − cells and the CD34 + CD38 − cells lacking CLEC12A expression, four MDS patients with known clonal cytogenetic abnormalities were selected for studies in the LTC‐IC assay.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of MDS mutations on HSCs are apparent in some mouse models 179 . For example, mutations in or loss of Dnmt3a or Tet2 expand the mutant HSC clone and increase HSC function at the expense of normal polyclonal hematopoiesis 75,77,180 .…”
Section: The Molecular Genetics Of Mdsmentioning
confidence: 99%
“…Genetic mouse models recapitulate hallmark features of human MDS—including multi-lineage peripheral blood cytopenias, dysmyelopoiesis, and variable propensities for transformation to acute leukemia [84]—and therefore represent useful in vivo models to investigate the reciprocal interactions between MDS cells and their BMME. Moreover, recent studies of the hematopoietic niche in mice have identified specific populations of mesenchymal stromal cells, osteoblastic lineage cells, and endothelial cells that are critical for HSPC support [916].…”
Section: Mesenchymal-osteolineage Dysfunction In Murine Models Of Mdsmentioning
confidence: 99%
“…NHD13 mice exhibit pathologic features of human MDS evidenced by multi-lineage blood cytopenias, dyspoiesis of erythroid, megakaryocytic and granulocytic cells and progression to acute leukemia [84, 88]. In studies of the NHD13 model, MSCs and OBCs were increased in the BMME of 18–23 week old NHD13 mice [89].…”
Section: Mesenchymal-osteolineage Dysfunction In Murine Models Of Mdsmentioning
confidence: 99%